2013
DOI: 10.1016/j.apradiso.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size, filler loadings and x-ray tube voltage on the transmitted x-ray transmission in tungsten oxide—epoxy composites

Abstract: The effect of particle size, filler loadings and x-ray tube voltage on the transmitted x-ray beam intensity by WO 3 -epoxy composites has been investigated using the mammography unit and a general radiography unit. Results indicate that nano-sized WO 3 has a better ability to attenuate lower x-ray energies (22 -35 kV) when compared to micro-sized WO 3 of the same filler loading. However, the role of particle size on transmitted x-ray beam intensity was negligible at the higher x-ray energy range (40 -120 kV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 10 publications
3
33
1
Order By: Relevance
“…The equivalent X-ray energies for the various X-ray tube voltages used were in the range of 17.5-60 keV, which conformed to our expectation since the equivalent X-ray energies for a mammography unit were 17.5, 19.6, 20.2 and 22.7 keV, which are the characteristic energies of molybdenum and rhodium, while the equivalent X-ray energy for a radiology unit is about one-third of the X-ray tube voltage used. The results showed that nano-sized WO 3 was more effective than micro-sized WO 3 in X-ray attenuation only in the low X-ray tube voltage range of 22-35 kV, but this size effect was not apparent at the higher X-ray operating tube voltage range of 40-120 kV [19]. Hence, the aim of this work was to verify our previous work on X-ray transmission in WO 3 -filled epoxy composites by using synchrotron radiations as the X-ray source for the characteristic (monochromatic) Xray energy range of 10-40 keV.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…The equivalent X-ray energies for the various X-ray tube voltages used were in the range of 17.5-60 keV, which conformed to our expectation since the equivalent X-ray energies for a mammography unit were 17.5, 19.6, 20.2 and 22.7 keV, which are the characteristic energies of molybdenum and rhodium, while the equivalent X-ray energy for a radiology unit is about one-third of the X-ray tube voltage used. The results showed that nano-sized WO 3 was more effective than micro-sized WO 3 in X-ray attenuation only in the low X-ray tube voltage range of 22-35 kV, but this size effect was not apparent at the higher X-ray operating tube voltage range of 40-120 kV [19]. Hence, the aim of this work was to verify our previous work on X-ray transmission in WO 3 -filled epoxy composites by using synchrotron radiations as the X-ray source for the characteristic (monochromatic) Xray energy range of 10-40 keV.…”
Section: Introductionmentioning
confidence: 57%
“…Hence, the aim of this work was to verify our previous work on X-ray transmission in WO 3 -filled epoxy composites by using synchrotron radiations as the X-ray source for the characteristic (monochromatic) Xray energy range of 10-40 keV. The results obtained were compared with those of previous work [19] to determine the equivalent energy range of the previous machines used (a mammography unit and a radiology unit). Materials Science and Engineering C xxx (2013) xxx-xxx 2.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations